2016
DOI: 10.1080/10538712.2015.1088915
|View full text |Cite
|
Sign up to set email alerts
|

Winning a Race: Narratives of Healing and Psychotherapy in Children and Adolescents Who Have Been Sexually Abused

Abstract: This article explores the process of recovering from sexual abuse according to children and adolescents who have been sexually abused and have successfully completed psychotherapy. In this qualitative study, interviews were conducted with 20 participants from 8 to 18 years of age and then subject to narrative analysis. Results show that participants' narratives of recovery involve an improvement of psychological well-being. Moreover, they feel better equipped to overcome future challenges, feeling empowered an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0
20

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 20 publications
4
42
0
20
Order By: Relevance
“…In this study, Capella et al (2016) found that patients interviewed towards the end of the therapy stated that they had healed from the abuse suffered, which they regarded as an achievement resulting from personal efforts, although they also acknowledged the presence of a context that fostered their recovery. In contrast, the present study found that only a minority of patients in the initial and middle stages of the therapy mentioned early changes related to the sexual abuse, without noting deeper changes linked to healing from the experience.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In this study, Capella et al (2016) found that patients interviewed towards the end of the therapy stated that they had healed from the abuse suffered, which they regarded as an achievement resulting from personal efforts, although they also acknowledged the presence of a context that fostered their recovery. In contrast, the present study found that only a minority of patients in the initial and middle stages of the therapy mentioned early changes related to the sexual abuse, without noting deeper changes linked to healing from the experience.…”
Section: Discussionmentioning
confidence: 78%
“…If this concept is linked to the present study, it could be hypothesized that this is what occurs in the initial stages of therapy: even though positive changes are identified in comparison to past moments, they do not involve the elaboration of the abusive experience. On the other hand, the final moments of the therapy process studied by Capella et al (2016) could be linked to a second narrative position proposed by Beiza et al (2015), which the authors label as healing narratives. Such narratives are characterized by the attribution of new meanings to the abusive experience and its integration into one's per- sonal history through a dynamic process of growth and change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Este aspecto resulta altamente relevante, pues introduce una perspectiva novedosa dentro de la literatura respecto de la recuperación en agresiones sexuales, que se ha centrado principalmente en el estudio de quienes han sido víctimas directas, especialmente de adultos victimizados en la infancia (Banyard, et al, 2001;Capella et al, 2016;Draucker et al, 2011).…”
Section: Conclusionesunclassified
“…Similar to pretend play, drawing and verbal communication are natural childhood manners of expression, which provides a space where children can feel comfortable (Brems, 2008; Midgley et al, 2009; Pace et al, 2015; Capella et al, 2016). Verbal production, finally, has an important role in assessing the psychological/mentalistic lexicon formed by terms referring to mental states.…”
Section: Introductionmentioning
confidence: 99%